Predictability of Hematological Parameters in the Diagnosis of Cesarean Scar Pregnancy - Dogru, Sukran; Atci, Asli Altinordu; Akkus, Fatih; Erdogan, Arif Caner; Acar, Ali (Journal of Laboratory Physicians, 2023)
Introduction Cesarean scar pregnancy (CSP) is an increasing clinical condition that causes serious maternal morbidity and mortality. This study aimed to evaluate if inflammation markers measured by hemogram can aid in the diagnosis of CSP.Materials and Methods A total of 86 patients were included in the study. The cases were divided as CSP (n: 42) and normal pregnancy (NP) (n: 44). At the time of admission, peripheral blood neutrophils, lymphocytes, monocytes, thrombocytes, systemic inflammatory index (SII) (neutrophil × platelet/lymphocyte), neutrophil–lymphocyte ratio, monocyte–lymphocyte ratio, and platelet–lymphocyte ratio were all measured. CSP and NP diagnoses were made by transabdominal or vaginal ultrasonography.Results In the CSP group, mean age (p < 0.001), gravida (p < 0.001), parity (p < 0.001), number of surviving children (p < 0.001), number of abortions (p < 0.001), cesarean number (p < .001), dilatation and curettage count (p = 0.013), monocyte (M) value (p = 0.039) and monocyte/lymphocyte value (MLR) (p = 0.035) were significantly higher than the control group. The optimal M value cut-off value was found to be > 0.40, the sensitivity value was 78.57, and the specificity value was 50.00. AUC = 0.632 (SE = 0.061) for the MLR value. The optimal MLR cut-off value was found to be > 0.232, the sensitivity value was 61.90, and the specificity value was 63.64.Conclusion Hemogram parameters, which are simple, inexpensive, and easily accessible, M and MLR are significantly higher in the diagnosis of CSP and can be used as an auxiliary parameter for ultrasonography.
Keywords: cesarean scar pregnancy; hemogram parameters; systemic inflammatory index